Trithuria brevistyla (Hydatellaceae), a new combination for the New Zealand endemic species from the South Island - de Lange, P.J.; Mosyakin, S.L. (Український ботанічний журнал, 2019)
A new combination, Trithuria brevistyla (K.A.Ford) de Lange & Mosyakin, is proposed for the recently described New Zealand, South Island endemic taxon originally published as T. inconspicua subsp. brevistyla K.A.Ford. Species rank for that taxon is advocated on the basis of morphological and reproductive distinctions between that species and the closely related North Island, New Zealand endemic T. inconspicua Cheeseman sensu stricto. Some general considerations on optional species versus subspecies ranks for plant taxa in need of conservation are provided.